1. A v (B -> C)
2. B / A v C
3.
Hello, Amber!
$\displaystyle \begin{array}{c}A \vee (B \to C)\\
B\qquad\qquad\quad \\ \hline
A \vee C\qquad\quad\end{array}$
I vaguely recall a theorem . . . the Law of Detachment (?)
. . $\displaystyle \begin{array}{c} p \vee q \\ \sim q\quad \\ \hline p\quad \end{array}$
The first line is: .$\displaystyle A \vee (B \to C) \quad\Rightarrow\quad A \vee (\sim\!B \vee C)\quad\Rightarrow\quad (A \vee C)\: \vee \sim\!B$
So the argument becomes: .$\displaystyle \begin{array}{c}(A \vee C)\:\vee\: \sim\!B \\ B\qquad\qquad \\ \hline \end{array}$
By the Law of Detachment, the conclusion is: .$\displaystyle A \vee C$